Sustainable synthesis of zwitterionic galactaric acid monoamides as monomers of hydroxylated polyamides. Issue 5 (13th June 2022) - Righetti, Grazia Isa. C.; Truscello, Ada; Li, Jiemeng; Sebastiano, Roberto; Citterio, Attilio; Gambarotti, Cristian
Abstract: A new and sustainable preparation of zwitterionic monoamides of galactaric acid is reported. The protocol consists of an efficient conversion of aldaric acid into the corresponding lactone and its further reaction in the presence of diamines, leading to the formation of the corresponding zwitterionic monoamides in high yields and selectivity. The zwitterions have been used as monomers to obtain the corresponding polyhydroxyamides. The overall protocol has shown a high atom economy, and all the carbon atoms present in the reagents are preserved.